Enriching cross-sectoral collaboration to foster inclusive cultures in schools: a Model to address the needs of diverse Chilean Students - Vidal, Veronica; Mendive, Susana; Gómez Zaccarelli, Florencia; Pozo-Tapia, Francisca; Narea, Marigen; Wachholtz, Daniela; Melo, Carolina (Frontiers in Psychology, 2024)
Inclusive education involves the interaction of diverse actors from different societal sectors, such as education, health, and policy. Inclusion laws and regulations in Chile are relatively new and have been taken as a regional model. However, the efforts to implement them have revealed some structural difficulties that must be discussed. This conceptual analysis article aims to provide insights to enrich cross-sectoral collaboration to foster inclusive cultures in Chilean schools. Considering the OECD Analytical Framework, which describes a systemic approach, we provide definitions for the critical components of the model and discuss the advances and challenges of current Chilean public policies in this field –including the Chile Crece Contigo and the School Integration Programs (SIP)—, the Chilean education system functioning, the social contexts, and students’ needs and supports based on the available evidence. Building from inclusive education literature and previous experiences, we delve into the model to address the needs of students with disabilities, social and cultural disadvantages, students belonging to the indigenous population, and students with a low socioeconomic level to propose action guidelines with a particular focus on integrating inclusive practices at the school level.